Mayan and Andean Medicine and Urban Space in the Spanish Americas - Fredrick, Sharonah (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2021)
Mayan and Andean medicine included empirical perspectives and botanical cures that were transmitted in the urban spaces of colonial Spanish America, spaces themselves built over former Amerindian cities. Mayan and Andean peoples, whose histories included development of both urban and rural aspects of civilization, brought their medical knowledge to the Hispanic cities of the colonial Americas. In these cities, despite the disapproval and persecution of the Inquisition, Native American medicine gradually became part of the dominant culture. As this article will demonstrate, Mayan and Andean medical knowledge was absorbed by the “new cities” that Imperial Spain constructed in the colonial Americas, church disapproval notwithstanding. Cities and urban space became prime conduits for the circulation and incorporation of Native American medical knowledge among the newer Hispanic and mestizo population in the colonial Americas.